On the recent action of the state with regard to venereal disease - McWeeney, E.J. (Statistical and Social Inquiry Society of Ireland, 1919)
"Syphilis and Gonorrhoea, respectively, the more serious and the less serious of those diseases, bear names which from the principle of association sound evilly to the ear. So, to, does the expression 'venereal disease,' which, by the way, is a misnomer, since it implies that the diseases are only contracted in sexual intercourse. Except in medical literature, these words have, until quite recently, been almost entirely tabooed, and the things they connote have for the most part been ignored." The veil has now been withdrawn and a flood of light thrown on the hidden canker that has been so long gnawing at the vitals of our modern civilisation. The moment seems opportune for a communication on the subject in view of the fact that our Public Health Authority here in Dublin is at present on the threshold of concerted action as against these diseases. In what follows I shall endeavour to give as clear an idea of the nature and extent of the evil as I can without going into those more technical details which are properly reserved for the medical profession.
Read January 24th, 1918
Keywords: Venereal disease; Public health policy; 314.15